Relationship Between Body Mass Index of Pregnant Women and Birth Weight of Babies with the Incidence of BGM in Infants - Nyna Puspita Ningrum (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Background: Poor nutritional conditions in infants that occur in a long time can affect the growth process of infants, the risk of immune system disorders, and the risk of infection that can end in death (Hong et al, 2006). BGM conditions that are not handled properly can run the risk of being stunted. Purpose: The purpose of this study was to analyze the relationship between the body mass index of pregnant women and birth weight of babies with the incidence of BGM in infants. Methods: This research method is quantitative analytic research with correlative study design approach. The populations were all infants and mothers of children under five in Siwalankerto village with total of 47 peoples; the sampling technique used was purposive sampling in accordance with the inclusion and exclusion criteria, so as to get 40 people. Data was tested for validity using the product moment validity test method. Results: Based on the results obtained with the chi square reliability test value of x count = 14.89 which is greater than the value of x table = 7.815 (for N = 40 respondents). So it can be concluded that there is a relationship between body mass index of pregnant women and birth weight of babies with the incidence of BGM in infants. Conclusion: Suggestions for health workers is to increase preventive efforts through approaches and counseling to the community in order to minimize the occurrence of malnutrition in pregnant women which can have an impact on children's health in the future.